(3YeOI GdcJGHI aj GdNW hGdcJGHI hGdCbdGe heG jJYdb HgG ef GdCOhGJs - (3jhSa Hf YHO Gddg GdRLGLj, CHh GdbGSe,J (B415 (3g` s
(3ChdgG (B:s
(3aEfj LeYJ aj gPG GdcJGH GdeSei HYeOI GdcJGHI hYf Phj GdCdHGH eG dGZfi ddcGJH Yfg s
(3BNQgG (B:s
(3hHYO GSbGWg GdLedI GdQGHYI jaVd CQHYhf gh MQa Gdeje hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1171s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI aDGO GdChd (B((3LGeYI GdbGgQI(B) (26178) s
Keywords: (3GdNW hCdGJgs